Analysis of risk factors for positive surgical margin after laparoscopic radical prostatectomy with and without neoadjuvant hormonal therapy - Wang, Fangming; Zhang, Gang; Tang, Yuzhe; Wang, Yunpeng; Li, Jianxing; Xing, Nianzeng (Frontiers in Endocrinology, 2023)
Background: Positive surgical margins (PSM) is not only an independent risk factor for recurrence, metastasis, and prognosis, but also an important indicator of adjuvant therapy for prostate cancer (PCa) patients treated with radical prostatectomy (RP). At present, there are few reports analyzing risk factors of PSM in laparoscopic RP (LRP), especially for those PCa cases who accepted neoadjuvant hormornal therapy (NHT). Hence, the aim of the current study was to explore risk factors for PSM after LRP in PCa patients with and without NHT. Methods: The clinicopathological data of patients who underwent LRP from January 2012 to July 2020 was retrospectively analyzed. Risk factors for PSM after LRP in NHT and non-NHT groups were respectively explored. Results: The overall PSM rate was 33.3% (90/270), PSM rate was 39.3% (64/163) in patients without NHT and 24.3% (26/107) in those with NHT. The apex was the most common location of PSM in non-NHT group (68.8%, 44/64), while the fundus was the most common location of PSM in NHT group (57.7%, 15/26). Multiple logistic regression revealed that body mass index (BMI), PSA, ISUP grade after LRP, pathological stage T (pT) and pathological lymph node status (pN) were independent factors affecting the PSM for patients without NHT (OR=1.